Prevalence and Factors Associated with Current Smoking Among Medical Students in Coastal South India - Ganesh Kumar, S; Subba, S H; Unnikrishnan, B; Jain, A; Badiger, S (Kathmandu University Medical Journal, 2012)
Background Smoking among health care personnel such as medical students is an important public health issue. More effective measures to reduce tobacco smoking among medical students are needed worldwide. Very few studies had been conducted in past in India and other developing countries to understand the magnitude of problem. Objectives To determine the prevalence and associated factors of current smoking among medical students. Methods Cross sectional study was conducted during January and February 2009 among 333 study subjects selected randomly from four batches of a teaching institution. Subjects were administered a self administered pre tested questionnaire and smoking status was assessed as per the criteria laid down by WHO. Proportion, chi square test and multiple logistic regression analysis were used for statistical analysis. Results The prevalence of current smoking was found to be 22.4% (67). There were widespread deficiencies in knowledge of smoking among students of different classes, as an important causal factor in many diseases like gastro intestinal malignancy, heart problems, asthma, and emphysema. It was found that only half of them were willing to quit smoking (33). Fourth year students (OR=2.54) and presence of peer pressure (OR=21.91) had independent significant association with current smoking. Conclusion Prevalence of smoking among medical students is high that warrants adoption of comprehensive smoking control interventions among them. DOI: http://dx.doi.org/10.3126/kumj.v9i4.6335 Kathmandu Univ Med J 2011;9(4):233-7